Lignin monomer conversion into biolubricant base oils. Issue 24 (26th November 2021) - Ebikade, Elvis Osamudiamhen; Sadula, Sunitha; Liu, Sibao; Vlachos, Dionisios G.
Abstract : Branched benzene lubricant and branched cyclic lubricant base oils were synthesized from lignin-derived monomers and aldehyde by hydroxyalkylation/alkylation and hydrodeoxygenation in high yields. Abstract : Despite progress in the depolymerization of lignin, only a few studies convert the obtained monomers to value-added products. Here we introduce a strategy to synthesize branched benzene lubricant (BBL) and branched cyclic lubricant (BCL) base oils from lignin-derived monomers and aldehyde. We perform carbon–carbon coupling via Brønsted acid-catalyzed hydroxyalkylation/alkylation (HAA) then hydrodeoxygenation (HDO). Optimum HAA reaction conditions achieve up to 90% guaiacol conversion and an HAA product containing 76% BBL and 24% enal condensation product over a P-SiO2 catalyst. Subsequent HDO of HAA products over an Ir-ReO x /SiO2 catalyst produces a lubricant-ranged mixture of BCL (C24 ) up to yield (82%) and small fractions of dodecyl cyclohexane and C10 and C15 carbons alkanes. The kinematic viscosity, viscosity index, and Noack volatility of these base oils are comparable to commercial petroleum-derived poly α-olefin Group IV and refrigerant base oils. This approach provides a sustainable pathway for replacing petroleum-derived base oils.